Sustainability assessment of electricity cogeneration from sugarcane bagasse in Jamaica. (1st November 2018) - Contreras-Lisperguer, R.; Batuecas, E.; Mayo, C.; Díaz, R.; Pérez, F.J.; Springer, C.
Abstract: Cogeneration from sugarcane bagasse in Jamaica represents a significant opportunity to reduce CO2 emissions and its dependence on a fossil fuel-based energy matrix. Generation of electricity through cogeneration is a huge opportunity in countries where the sugarcane industry is in decline. This article draws on the findings of a case-study on electricity generation through cogeneration in Jamaica to provide some key messages that may be useful for policy-makers and the private sector to make electricity generation by cogeneration a more competitive option the for investors. To this end, this article analyses two scenarios: the first is a Baseline Scenario that assesses the impact of cogeneration technology already installed in a Jamaican sugarcane company where the cogeneration stage produces 2, 2 MW; the second one considers that the cogeneration technology is changed to a new biomass based power plant upgrading the cogeneration stage in order to produce 5 MW of power from bagasse. The assessment was carried out by using a complete Life Cycle Assessment, Life Cycle Costing and Social Life Cycle Assessment. The results revealed that generation of electricity from cogeneration derived from bagasse is a suitable alternative adding economic, environmental and social value.